1997
DOI: 10.1063/1.364371
|View full text |Cite
|
Sign up to set email alerts
|

High temperature optical properties of cadmium telluride

Abstract: The high temperature optical properties of cadmium telluride have been studied at temperatures up to 1104 K by measurement of the incandescence spectra from a wafer of that material. These measurements provided information equivalent to that of a transmission experiment and allowed the optical absorption spectra of the material to be determined using a theoretical expression for the refractive index and its dispersion with wavelength modified to account for the effect of temperature. This analysis required onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…Mullins et al [32] found E e ¼ 9 70:4 meV for a wafer of CdTe, which is too much smaller than our values. The difference between our results and their result may be due to the difference in preparation techniques and film thickness.…”
Section: Optical Propertiescontrasting
confidence: 80%
“…Mullins et al [32] found E e ¼ 9 70:4 meV for a wafer of CdTe, which is too much smaller than our values. The difference between our results and their result may be due to the difference in preparation techniques and film thickness.…”
Section: Optical Propertiescontrasting
confidence: 80%
“…b is listed in Table . The E U increases monotonically from about 27 meV before annealing to 29 meV after 15 min annealing, illustrating a gradual increase in the structural disorders in the CdTe film or its surface . Interestingly, this trend is accelerated at longer annealing times beyond 15 min.…”
Section: Resultsmentioning
confidence: 91%
“…a. After annealing, changes in the tail of absorption band where residual absorption is anticipated are observed and can be characterized by the Urbach energy E U . According to the Urbach rule, the optical absorption coefficient α can be obtained by α=α0 exp(hν/EnormalU). …”
Section: Resultsmentioning
confidence: 99%
“…The minimum T of the visible light at wavelengths <800 nm is about 15%, for both types of samples, which is consistent with the absorption anticipated for the CdTe films with 1.2 microns thickness. 15 However, different absorption edges are clearly seen at the wavelength range of 810–840 nm for the as-deposited and 830–860 nm for cell samples, respectively.…”
Section: Resultsmentioning
confidence: 99%